The Relationship between Islamic Law and the Concept of Gender Equality Based on Maqasid Sharia Perspective - Rismilda, Nela Aprilia (Yayasan Sinergi Kawula Muda, 2023)
This study aims to determine the relationship between Islamic law and gender equality using the maqashid sharia approach. Gender equality is a concept that refers to the granting of equal rights, responsibilities, and opportunities to all individuals regardless of gender whether male or female which covers various aspects of life. This research analyzes the relationship between Islamic law as the main law of Islam and gender equality, which is a concept in all religions that is drawn using the maqashid sharia perspective. The research method used is qualitative literature that uses maqasid sharia studies as the primary data source and secondary data such as literature related to the studies discussed. The results show that in the perspective of maqasid sharia, gender equality in Islamic law holds the main principle of maintaining the benefit and justice as well as the maintenance of the five principles of maqashid sharia consisting of hifdz ad-din, hifdz an-nafs, hifdz al-aql, hifdz al-nasl, and hifdz al-mal.